Squamous Cell Carcinoma Arising from an Oral Lichenoid Lesion: A Case Report - Ali Taghavi Zenouz; Masoumeh Mehdipour; Rana Attaran; Ayla Bahramian; Paria Emamverdi Zadeh (Tabriz University of Medical Sciences, 2012)
Lichenoid reactions represent a family of lesions with different etiologic factors and a common clinical and histologic appearance. Lichen planus is included with lichenoid reactions and is a relatively common chronic mucocutaneous disorder. The most important complication of lichenoid reactions is the possibility of malignant transformation. That is why it has been considered a precancerous condition. Although the malignant transformation rate varies widely in the literature, from 0.4 to 6.5 percent, in most studies it does not exceed 1%. The aim of this paper is to report a rare case of squamous cell carcinoma (SCC) arising within an oral lichenoid lesion in a 17-year-old woman, where SCC is very uncommon. The patient did not have any risk factors and was healthy. The lesion was located on the border of the tongue. In view of the common occurrence of OLP (oral lichen planus) and the unresolved issues regarding its premalignant potential, this case report illustrates the need for histologic confirmation and a close follow-up of clinical lesions with lichenoid features.